2020
DOI: 10.36108/pajols/0202/40(0240)
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological Alterations In Organs of Nile Tilapia Fingerlings Exposed To Sub-Lethal Concentrations of Aqueous Crude Leaves Extract of Desert Date

Abstract: Background: Histopathological changes have been widely used as biomarkers in determining the effects of pollutants on fish. Leaves of Balanites aegyptiaca, a deep-rooted, evergreen or semi-deciduous, multi-branched, spiny tree have been reported to have pesticidal, anaesthetic and ichthyotoxic effects. This study sought to find out the effect of sub-lethal concentrations (5.00, 11.00, 21.00, 43.00, and 86.00 mg/L) of B. aegyptiaca on histopathology of gills, kidney, and liver of mixed-sex Oreochromis niloticus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 15 publications
3
5
0
Order By: Relevance
“…The grades in the severity of hepatic lesions (hepatocellular degeneration, sinusoidal congestion and cellular infiltration) observed in this study have further validated the hepatic enzymes results earlier stated and could reflect a remarkable derangement in the normal functioning of the liver. These observations on hepatic histopathological lesions are in agreement with similar studies reported by Audu et al, [12,39].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The grades in the severity of hepatic lesions (hepatocellular degeneration, sinusoidal congestion and cellular infiltration) observed in this study have further validated the hepatic enzymes results earlier stated and could reflect a remarkable derangement in the normal functioning of the liver. These observations on hepatic histopathological lesions are in agreement with similar studies reported by Audu et al, [12,39].…”
Section: Discussionsupporting
confidence: 93%
“…This is in line with the findings of Kumar et al, [37] after exposing Heteropneustes fossilis to varied concentrations of Neem extract, Azadirachtin. Gill lesions (lamella cell depletion and complete histo-architectural distortion) observed in the present study corroborate the observations of [38,39,12]. Similar lamella depletion has also been reported by Kumar et al, [37].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations